2014
DOI: 10.1159/000358240
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Toll-Like Receptor-Induced Cytokine Profiles in the Blood and Cerebrospinal Fluid of Chikungunya Patients

Abstract: Background: Chikungunya infection caused by Chikungunya virus (CHIKV) is an inflammatory disease affecting the joints and may also lead to neurological complications. We investigated a panel of human Toll-like receptor (TLR)-induced cytokines in Chikungunya patients with and without neurological complications. Methods: In a case-control study, a panel of 12 cytokines and chemokines, TNF-α, IFN-α, IL-1β, IL-6, IL-12, IL-17A, IL-8, monocyte chemotactic protein (MCP)-1, RANTES, interferon (IFN)-γ-induced protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 32 publications
1
16
0
1
Order By: Relevance
“…Of the 14 studies identified, 5 were excluded from the meta-analysis because their data could not be extracted for analysis: in 1 study, the results from the cytokine assay were presented as optical density readings and could not be computed into concentration values [ 26 ]; another study contained data from only a single patient [ 28 ]. To overcome the lack of immune mediator profiles from non-CHIKV controls in this study, we used the data from healthy controls in a previously published study [ 24 ] as a reference to perform the analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 14 studies identified, 5 were excluded from the meta-analysis because their data could not be extracted for analysis: in 1 study, the results from the cytokine assay were presented as optical density readings and could not be computed into concentration values [ 26 ]; another study contained data from only a single patient [ 28 ]. To overcome the lack of immune mediator profiles from non-CHIKV controls in this study, we used the data from healthy controls in a previously published study [ 24 ] as a reference to perform the analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Five of the 14 studies were excluded from the meta-analysis because their data could not be extracted for analysis. In 1 study, data were presented as optical density readings and could not be computed into concentration values [ 26 ]; 1 study contained data from only a single patient [ 28 ]; 2 studies provided only the median or mean of the control group without any estimates of the variance [ 25 , 27 ]; and 1 study provided median values with interquartile ranges for the patient and control groups [ 33 ]. Nevertheless, apart from the single-patient study [ 26 ], fold changes were computed for these studies, and they were depicted in the heat maps but not used in the meta-analysis.…”
Section: Methodsmentioning
confidence: 99%
“…A study from India compared the cytokine profile for patients with and without neurological complications following chikungunya infection . Of those with neurological disease, 4 had encephalitis and 1 had “neuropathy.” Concentrations of 4 cytokines (TNF‐α, IFN‐α, IL‐6, and monokine induced by IFN‐γ) were found to be significantly higher in patients with neurological disease secondary to chikungunya, as opposed to uncomplicated chikungunya infection.…”
Section: Neurological Manifestationsmentioning
confidence: 99%
“…CHIKV is known to target human epithelial and endothelial cells, fibroblasts and macrophages [13][14][15], as well as human muscle satellite cells [16]. The virus is also suspected of neurotropism [17,18], which can lead to neurological complications [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%